Dari Anyaman ke Ketahanan: Integrasi Ekonomi Kreatif–SLF pada Komunitas Bambu Cikiray, Kabupaten Tasikmalaya - Susanto, Laela; Karismatika, Anggi Permata (Jurnal EMT KITA, 2026)
The creative economy drives sustainable development; among its subsectors, crafts, particularly bamboo weaving, contribute to household welfare and the preservation of local culture. This study analyzes the impact of bamboo craft on the welfare of households in Kampung Cikiray by examining the five livelihood capitals through a PAR–SLF approach. Data from 45 respondents were collected via a Likert‐scale questionnaire, focus group discussions (FGDs), interviews, and observation. Quantitative analysis comprised descriptive statistics (mean, median, SD, IQR) and 95% Wilson confidence intervals for proportions; pre–post comparisons used paired t-tests or Wilcoxon signed rank tests with effect sizes. Qualitative data were examined using reflexive thematic analysis with method and source triangulation. Results indicate that approximately 80% of households earn IDR 0.5–2.5 million/month. Following the intervention, full participants experienced ≈15–20% income gains. About ≈42% undertook product innovation/diversification (e.g., bags, lampshades, décor) and adopted digital marketing. Strengthening was confirmed in cooperatives (social capital), bamboo rotation and replanting (natural capital), tools and digital access (physical capital), and savings/microcredit (financial capital). Theoretically, the findings affirm PAR–SLF as a diagnosis, action, and evaluation pathway for reinforcing the five capitals. Practically, an upstream-downstream package resource governance and quality standards; tiered training in technique, design, QC, and digital marketing; collective marketing/branding; and access to finance most effectively guide the village toward an inclusive, resilient, and sustainable future.